2013
DOI: 10.1002/jgra.50215
|View full text |Cite
|
Sign up to set email alerts
|

Statistical study of geomagnetic field line resonances observed by CHAMP and on the ground

Abstract: [1] Studies of single events showing the signatures of Pc3 pulsation field line resonances (FLRs) observed in magnetic field data by CHAMP above the E-region ionosphere and at conjugate ground stations at L < 2 have previously been reported. Notable features of FLRs observed in these investigations were a Doppler shift in the satellite azimuthal component and a 90 rotation of the polarization ellipse between CHAMP and the ground. In this report, we extend the previous work by means of the first statistical inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
(128 reference statements)
1
16
0
Order By: Relevance
“…Previous studies have shown that Pc3–4 waves propagate into the low‐ L ( L = 2–3) dayside magnetosphere and low‐latitude ground stations as fast mode waves (Kim & Takahashi, ). The conjunction of observations from LEO satellites and ground magnetometers demonstrated that compressional Pc3–4 waves observed during daytime propagate to midlatitudes and become the driver of field line resonances (Heilig et al, ; Ndiitwani & Sutcliffe, ; Vellante et al, ). Field line resonance is impeded at near‐equatorial latitudes since the damping rate increases sharply there (Yumoto et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that Pc3–4 waves propagate into the low‐ L ( L = 2–3) dayside magnetosphere and low‐latitude ground stations as fast mode waves (Kim & Takahashi, ). The conjunction of observations from LEO satellites and ground magnetometers demonstrated that compressional Pc3–4 waves observed during daytime propagate to midlatitudes and become the driver of field line resonances (Heilig et al, ; Ndiitwani & Sutcliffe, ; Vellante et al, ). Field line resonance is impeded at near‐equatorial latitudes since the damping rate increases sharply there (Yumoto et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The coordinated low-altitude satellite (CHAMP) and ground observations of Pc3-4 waves indicated on a significant contribution of compressional component into the wave structure in the upper ionosphere (Heilig et al, 2007). Pc3-4 waves demonstrated a localized enhancement of transverse components at midlatitudes attributed to the field line resonance, where the frequency of compressional mode transporting the wave energy from extra-magnetospheric source matches the local frequency of Alfven eigenoscillations (Vellante et al, 2004;Ndiitwani and Sutcliffe, 2009;Heilig et al, 2013). Away from the resonant region, the structure of Pc3-4 waves in the upper ionosphere was dominated by the compressional mode.…”
Section: Introduction: Possible Mechanisms Of Pi2/pc3 Wave Propagatiomentioning
confidence: 99%
“…However, a mechanism of such amplification has not been unambiguously identified yet. Possible mechanisms can involve enhancement of the ionospheric currents induced by mid-latitude Alfven wave which spread into the equatorial region with elevated ionospheric Cowling conductance (Shinohara et al, 1997); or direct penetration of compressional wave towards the near-equatorial region without conversion into Alfven field line oscillations (Yumoto and Saito, 1983;Heilig et al, 2007Heilig et al, , 2013. Most probably, combination of all these mechanisms takes place, and to resolve them is a challenging goal.…”
Section: Introduction: Possible Mechanisms Of Pi2/pc3 Wave Propagatiomentioning
confidence: 99%
“…Vellante et al (2004), Ndiitwani and Sutcliffe (2009), and more recently Heilig et al (2013) demonstrated the apparent shift in frequency of the shear Alfvén wave component of the pulsations due to rapid motion of CHAMP with respect to the ground stations. Waters et al (1991) introduced the cross-phase method to identify field line resonant frequencies from phase spectra from a pair of meridional ground stations.…”
Section: P R Sutcliffe Et Al: Spectral Structure Of Pc3-4 Pulsatiomentioning
confidence: 93%